2018
DOI: 10.1016/j.schres.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Negative voice-content as a full mediator of a relation between childhood adversity and distress ensuing from hearing voices

Abstract: A key predictor of whether or not an individual who hears voices (auditory verbal hallucinations; AVH) meets criteria for a psychiatric diagnosis is the level of negative content of the voices (e.g., threats, criticism, abuse). Yet the factors that contribute to negative voice-content are still not well understood. This study aimed to test the hypotheses that levels of childhood adversity would predict levels of negative voice-content, and that negative voice-content would partially mediate a relation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
(63 reference statements)
4
21
0
Order By: Relevance
“…The presence of positive hallucinations should also alert us to the possibility of other pathways. Rosen et al 44 have found that negative voice-hearing is a full mediator of a relationship between childhood adversity and distress that may arise from hearing voices. Nonclinical voice-hearers report more positive and more controllable experiences than do their clinical counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of positive hallucinations should also alert us to the possibility of other pathways. Rosen et al 44 have found that negative voice-hearing is a full mediator of a relationship between childhood adversity and distress that may arise from hearing voices. Nonclinical voice-hearers report more positive and more controllable experiences than do their clinical counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…; Rosen et al . ), with evidence that voices are a meaningful defensive response to adversity (Longden ), and likely to be reflective of past negative experiences (Rosen et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…), with evidence that voices are a meaningful defensive response to adversity (Longden ), and likely to be reflective of past negative experiences (Rosen et al . ). People who hear voices develop a relationship with their voices: the nature of both the relationship (Beavan ; Romme & Escher ) and the content of the voices determines whether or not distress is experienced (McCarthy‐Jones et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small sample size also prevented us from exploring whether diagnostic group (BPD vs. SZ) moderated the associations found between interpersonal schemata, appraisals of voices, and depression, although the PROCESS macro of Hayes [45] includes the option to examine conditional indirect effects. In addition, given the small sample size, we did not consider it appropriate to use negative voice content as a covariate in the mediation analyses, even though it has been found to influence both appraisals of voices and distress in voice hearers in our sample [29] and in previous studies [19,27,66,67]. Likewise, we did not consider the severity of positive and negative symptoms as a covariate in our analyses, even though the "psychosis as primary" model argues that interpersonal schemata and depression result from the psychotic process itself [17].…”
Section: Discussionmentioning
confidence: 95%